Editorial perspective: a plea for the sustained implementation of digital interventions for young people with mental health problems in the light of the COVID-19 pandemic - Kaess, Michael; Moessner, Markus; Koenig, Julian; Lustig, Sophia; Bonnet, Sabrina; Becker, Katja; Eschenbeck, Heike; Rummel-Kluge, Christine; Thomasius, Rainer; Bauer, Stephanie (The journal of child psychology and psychiatry, 2021)
The coronavirus disease 2019 pandemic and the consequent global lockdown posed a particular challenge for youths with mental health problems. Crucial interference with their everyday lives likely increased psychological distress while accessibility of conventional mental health care was limited. Ongoing online trials offer a unique opportunity to analyse mental health status and help-seeking behaviour of adolescents during the pandemic. The ProHEAD-online trial aims at improving help-seeking behaviour of children and adolescents with significant psychological impairment. From January to May 2020, 1,042 students had access to the ProHEAD-online platform providing information on mental illness, monitoring, peer support and professional counselling. In the week from 11 March, when schools were closed in Germany, a drastic (more than 2 standard deviations) but time-limited increase in utilization of the ProHEAD-online services became apparent. This may indicate a worsened mental health status and an increased help seeking via digital services during the lockdown. Although this finding is purely observational, it speaks to the importance of evidence-based online service in the field of mental health within the current crisis and beyond.
Zuerst publiziert: 14. September 2020
Gesehen am 06.10.2025